À l’origine du « rang » canadien - Derruau, Max (Cahiers de géographie du Québec, 1956)
What is the origin of the type of settlement known in French speaking Canada as the rang ? Is it an import from France or an original Canadian creation ? The System is based on French agricultural customs, but bas been adapted to theNew World and applied with a geometrical strictness unknown in France.